Detailed modeling of positive selection improves detection of cancer driver genes - Siming Zhao (Nature Portfolio, 2019)
Finding driver genes sheds lights on the biological mechanisms propelling the development of a tumour, and can suggest therapeutic strategies. Here, the authors develop driverMAPS, a model-based approach to identify driver genes, and apply it to TCGA datasets.